Semen collection, semen analysis and artificial insemination in the kakapo (Strigops habroptilus) to support its conservation - Fischer, Dominik; Schneider, Helena; Eason, Daryl; Bublat, Andreas; Vercoe, Deidre; Robertson, Fiona; Robertson, Bruce C.; Digby, Andrew; Lierz, Michael; Justus Liebig University Giessen (My University, 2025)
The critically endangered kākāpō (Strigops habroptilus) has suffered population declines due to habitat loss, hunting, and predation. Conservation efforts, including translocation to predator-free islands, have helped increase numbers of this flightless parrot from 51 individuals in 1995–142 in 2019. However, low fertility and high embryo mortality, likely due to genetic bottlenecks continue to hinder population growth. This is further aggravated by the kākāpō’s lek mating system, which allows only a minority of males to father a disproportionate number of offspring, resulting in 21% of non-reproductive males. The study aimed to enhance assisted reproduction techniques to assess male fertility, increase egg fertility, and ensure genetic diversity. Artificial insemination (AI) was used to mimic a second copulation, as females mating with multiple males show higher fertility rates. During the 2019 breeding season, semen collection was successful in 20 males and in 93.5% of 46 attempts using abdominal massage method and electric stimulation technique. Semen volume, colour, consistency, contamination, pH and the motility, concentration, viability and morphology of spermatozoa were analysed. Ejaculate volume ranged between 0.1 and 210 μl and the mean pH was 7.5 ± 0.4 (x ± SD). Average sperm viability was 87.4 ± 10.0% with a total motility of 60.9 ± 22.0% and a progressive motility of 28.3 ± 19.8%. AI was performed 15 times in 12 females, improving second clutch fertility (70% vs. 29.4% without AI). Egg fertility in the second clutch without AI was 29.41% (5/17) compared to 70% (14/20) after AI. Paternity testing confirmed AI offspring (four chicks of three females), including from two previously non-reproductive males, enriching the gene pool with rare alleles (e.g., genes from Fiordland founding population). This study demonstrates the value of assisted reproduction in conserving endangered avian species by improving reproductive success and preserving genetic diversity.
Keywords: ddc:630